2022
DOI: 10.3390/ijms23052693
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Damage via Non-Photochemical Quenching, Phenolic Compounds and Photorespiration in Ulva prolifera Induced by Low-Dose and Short-Term UV-B Radiation

Abstract: The Yellow Sea green tide (YSGT) is the world’s largest transregional macroalgal blooms, and the causative species Ulva prolifera (U. prolifera) suffers from ultraviolet-b radiation (UVBR) during the floating migration process. Previous study confirmed that U. prolifera displayed a wide variety of physiological responses characterized as acclimation to UVBR, while the response mechanisms against low-dose and short-term radiation (LDSTR) are not clear. A study with photosynthetically active radiation (PAR) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…GO, as a key enzyme of photorespiration, plays an important role in maintaining the reduction equivalent of the thalli [35,56]. The important role of photorespiration in the adaptation of U. prolifera to stresses has been demonstrated in our previous studies [43]. In the present study, under HL conditions, AOX regulated the redox equivalent within the photosynthetic system by modulating the photorespiration process with GO as the key enzyme, so as to avoid an excessive reduction equivalent and optimize the photosynthetic activity of the thalli.…”
Section: Relationship Among Aox Photosynthesis and Photorespirationmentioning
confidence: 63%
See 2 more Smart Citations
“…GO, as a key enzyme of photorespiration, plays an important role in maintaining the reduction equivalent of the thalli [35,56]. The important role of photorespiration in the adaptation of U. prolifera to stresses has been demonstrated in our previous studies [43]. In the present study, under HL conditions, AOX regulated the redox equivalent within the photosynthetic system by modulating the photorespiration process with GO as the key enzyme, so as to avoid an excessive reduction equivalent and optimize the photosynthetic activity of the thalli.…”
Section: Relationship Among Aox Photosynthesis and Photorespirationmentioning
confidence: 63%
“…GO activity can be used to indicate the photorespiration flux [55,56]. Our previous research has confirmed that GO activity is positively correlated with other key enzymes, namely serine: glyoxylate aminotransferase (SGAT) and glycerate kinase (GLYK), in the photorespiration pathway when U. prolifera is exposed to short-term and low-intensity UVB radiation [43]. In addition, rice plants induced by antisense GO showed an obvious photorespiration defect phenotype [57], and in related research on Jatropha curcas plants under severe drought stress, GO activity was used to further verify the occurrence of photorespiration [58].…”
Section: Relationship Among Aox Photosynthesis and Photorespirationmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, it is possible that in F4, the applied acute UV-B resulted in a negative stress due to the lack of other co-occurring stresses, as demonstrated in a recent study where the UV-B acted as a ‘positive stress’ when it was presented with another abiotic variable [ 31 ]. Consistently, F4 exposed to continuous acute UV-B (1.7 W m −2 ) for 18 h resulted in a significant decline of the photosynthetic activity, indicating that this acute UV-B dose induced photoinhibition probably due to the imbalance of pro-oxidant production and scavenging capacity in F4 cells [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, TAC content was maintained at control levels during the experimental period, indicating that these non-enzymatic antioxidants were still functioning and were important during UV-B acclimation. Since enzymatic and non-enzymatic antioxidants may have a good complementary function in the protection of cells from UV-induced photo-oxidative damage [ 9 , 32 , 35 ], it would be interesting to identify those metabolites involved in LG1 photoacclimation.…”
Section: Discussionmentioning
confidence: 99%